Protein-Eye View of the in Meso Crystallization Mechanism - van T Hag, Leonie (Langmuir : the ACS journal of surfaces and colloids, 2019)
For evolving biological and biomedical applications of hybrid protein?lipid materials, understanding the behavior of the protein within the lipid mesophase is crucial. After more than two decades since the invention of the in meso crystallization method, a protein-eye view of its mechanism is still lacking. Numerous structural studies have suggested that integral membrane proteins preferentially partition at localized flat points on the bilayer surface of the cubic phase with crystal growth occurring from a local fluid lamellar L? phase conduit. However, studies to date have, by necessity, focused on structural transitions occurring in the lipid mesophase. Here, we demonstrate using small-angle neutron scattering that the lipid bilayer of monoolein (the most commonly used lipid for in meso crystallization) can be contrast-matched using deuteration, allowing us to isolate scattering from encapsulated peptides during the crystal growth process for the first time. During in meso crystallization, a clear decrease in form factor scattering intensity of the peptides was observed and directly correlated with crystal growth. A transient fluid lamellar L? phase was observed, providing direct evidence for the proposed mechanism for this technique. This suggests that the peptide passes through a transition from the cubic QII phase, via an L? phase to the lamellar crystalline Lc phase with similar layered spacing. When high protein loading was possible, the lamellar crystalline Lc phase of the peptide in the single crystals was observed. These findings show the mechanism of in meso crystallization for the first time from the perspective of integral membrane proteins